2000
DOI: 10.1128/jcm.38.12.4425-4429.2000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diarrheagenic Escherichia coli in Finns with or without Diarrhea during a Round-the-World Trip

Abstract: The incidence of diarrhea and the prevalence of bacterial enteropathogens, viruses, and parasites in feces of subjects with and without diarrhea were evaluated in 204 Finns traveling round the world (from Finland to China, Malaysia, Australia, Fiji, Chile, and Brazil and back to Finland). Special emphasis was placed on the finding of diarrheagenic Escherichia coli (enterotoxigenic, enteropathogenic, Shiga toxin-producing, and enteroaggregative strains) by PCR from growth on primary culture plates. From the PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 24 publications
6
24
1
Order By: Relevance
“…in Mozambique and Nigeria [14,15]. In our study, EAEC was the most commonly detected DEC pathogroup in both groups of children, suggesting that EAEC is not associated with diarrhoea, as also suggested by other recent studies [13,16]. However, some researchers have found EAEC to be associated with diarrhoea [17,18].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…in Mozambique and Nigeria [14,15]. In our study, EAEC was the most commonly detected DEC pathogroup in both groups of children, suggesting that EAEC is not associated with diarrhoea, as also suggested by other recent studies [13,16]. However, some researchers have found EAEC to be associated with diarrhoea [17,18].…”
Section: Discussionsupporting
confidence: 83%
“…The mixture was boiled for 10 min and centrifuged for 1 min at 11337 g and the supernatant was analysed in the PCR reactions. One microlitre of the supernatant was added to 9 lL reaction mixture containing 0.16 U Taq DNA polymerase (Finnzymes, Espoo, Finland), 2 lL of 5 · GC buffer, 0.24 lL 25 mM MgCl 2, 0.4 lL of a mixture of the four DNA deoxynucleotide triphosphates (5 mM each) and PCR primers at the concentrations listed in Table 1 [13]) and the E. coli-negative control RH E6715 (ATCC25922) were included in each PCR run.…”
Section: -Plex Pcr For Decmentioning
confidence: 99%
“…The present study showed a high level of occurrence of EAEC and LT-ETEC among the controls, at 16% and 22%, respectively. In developing countries, the non-symptomatic carriage of EAEC and other pathogroups of E. coli has already been noted [23]. These high rates of carriage among our controls may be explained by the high sensitivity of the new PCR assays.…”
Section: Discussionsupporting
confidence: 50%
“…There is increasing evidence that polymicrobial infections in which microorganisms present specific pathologies may act in a synergistic or inhibitory fashion, impacting on either tissue, host cell destruction or the maintenance of health [6]. Among these, pathogen with better conditions to invade the intestine and cause diarrhoea [7].…”
Section: Introductionmentioning
confidence: 99%